Child-therapist and parent-therapist alliances and outcome in the treatment of children with oppositional defiant/conduct disorder. (19th May 2023) - Dose, Christina; Thöne, Ann-Kathrin; Del Giudice, Teresa; Görtz-Dorten, Anja; Faber, Martin; Benesch, Christina; Hautmann, Christopher; Lindenschmidt, Timo; Döpfner, Manfred
Abstract: Objective: This study examined the quality of therapeutic alliance from different rater perspectives (child, parent, therapist) in cognitive behavioural therapy for children with oppositional defiant disorder (ODD) and conduct disorder (CD), and its association with symptom severity. Further, a panel model with an autoregressive cross-lagged panel design was used to explore whether therapist-rated and parent-rated therapeutic alliance influences change in symptom severity, or vice versa. Methods: Sixty boys aged 6–12 years with a principal diagnosis of ODD/CD, and their parents, received individually delivered social competence training for childhood aggressive behaviour problems. Child, therapist, and parent ratings of therapeutic alliance and symptom severity were measured twice. Results: Our results indicate good to very good therapeutic alliance that was relatively stable over time. The cross-sectional analyses of the alliance-symptom association revealed moderate correlations. However, effects of early alliance on later treatment outcome or of early symptom severity on later alliance were marginal. The only significant association was found between early parent-rated therapist-parent alliance and later parent-rated symptom severity. Conclusion: Our study shows a moderate correlation between simultaneously assessed therapeutic alliance and symptoms. The findings of the panel model indicate that an early good therapeutic alliance is a component of later therapeutic success (parent perspective).